2019
DOI: 10.1111/jbg.12403
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome analysis identifying candidate genes of altitude adaptive ecological thresholds in yak populations

Abstract: The domestic yak (Bos grunniens) is an iconic symbol of animal husbandry on the Qinghai-Tibet Plateau. Long-term domestication and natural selection have led to a wide distribution of yak, forming many ecological populations to adapt to the local ecological environment. High altitude is closely related to oxygen density, and it is an important environmental ecological factor for biological survival and livestock production. The aim of the present study was to perform a preliminary analysis to identify the cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Yaks at sea level and at altitudes of 2260−4500 m exhibit lower pulmonary artery pressures (Ishizaki et al, 2005). Genomic analysis of yaks indicates several HIF-specific mutations have occurred in high vs. low altitude populations, including to two important regulators of HIF (ADAM17 and ARG2) (Qiu et al, 2012(Qiu et al, , 2015Guang-Xin et al, 2019). Furthermore, transcriptomic analysis of yaks endemic to an altitudinal gradient demonstrated that EPAS1 expression increases with altitude (Qi et al, 2019).…”
Section: Animals Domesticated High-altitude Mammal Populationsmentioning
confidence: 99%
“…Yaks at sea level and at altitudes of 2260−4500 m exhibit lower pulmonary artery pressures (Ishizaki et al, 2005). Genomic analysis of yaks indicates several HIF-specific mutations have occurred in high vs. low altitude populations, including to two important regulators of HIF (ADAM17 and ARG2) (Qiu et al, 2012(Qiu et al, , 2015Guang-Xin et al, 2019). Furthermore, transcriptomic analysis of yaks endemic to an altitudinal gradient demonstrated that EPAS1 expression increases with altitude (Qi et al, 2019).…”
Section: Animals Domesticated High-altitude Mammal Populationsmentioning
confidence: 99%
“…In the yak populations, several genes putatively associated with adaptation to life at high altitudes were identified. These genes are primarily related to physiological pathways in response to hypoxia and temperature acclimatization and modifications of the cardiovascular system and energy metabolism [13,20,56]. Endothelial PAS domain-containing protein 1 (EPAS1) is the top candidate gene encoding the hypoxia-inducible transcription factor (HIF-2α).…”
Section: Genetic Background Of High-altitude Adaptationsmentioning
confidence: 99%
“…Camk2b, Gcnt3, Hsd17b12, Whsc1, and Glul High level of nutrition utilization in high altitudes [13] HIF1A, MMP3, ADAM17, ARG2 High-altitude adaptation [13] DEXI, DCC, and MRP4 Adaptation to high-altitude environments [14] PDE4D, RPS6KA6, ITPR1, and GNAO1 Environmental information processing and environmental adaptability [20] EPAS1 Key transcription factor that activates the expression of oxygen-regulated genes [21] ABCG8, COL4A1, LOC102287650, PDCD1, and NUP210 Adaptation to high-altitude environments [22] VEGF-A Regulation of blood vessel size [35] MMP3…”
Section: Candidate Genes Functions Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…ET can be recognized both in time series analysis and in spatial comparison of environmental gradients [20][21][22]. ET studies have become a hot issue in recent years with the development of sustainability research [23][24][25]. The threshold analysis method is popular in evaluating the nonlinear response of environment changes.…”
Section: Introductionmentioning
confidence: 99%